Valuation of algorithms in transfer pricing - Inki, Joonas (My University, 2019)
The purpose of this study is to make valuation of intellectual properties in transfer pricing in global organization. The target of valuation is two algorithms in research and development projects, which are utilizing artificial intelligence and machine learning technology, and both will come into commercial use, but the valuations only come into internal use. The transfer pricing is used in intra-group transactions and fiscal reasons the valuation of algorithms must follow arm’s length principle. An essential principle in transfer pricing is that it must be following arm’s length principle. That means the target of transfer pricing should set the price like it would be on sale for anybody in the open market. The making of valuation of algorithms is complicated and challenging due its uniqueness. There are not necessarily comparable algorithm technologies exist or it is not available in the open market where they could be compared in transfer pricing. For the successful value determination of algorithms is to make familiar with valid Finnish legislation and OECD guidelines of transfer pricing. In addition, the study requires the practical knowledge of valuation methods of transfer pricing and researching relevant material received from case organization. There are several methods to make valuation about algorithms, so the choice of right method and good argumentation by using substance is important for reaching enough mutual understanding with tax authority. The empirical studies require interviewing the relevant personnel of the company, utilizing current financial data and using the previous theoretical substance what has brought out in the study. When the taxpayer and tax authority have same insight about fair value of the target of transfer pricing, thus both parties avoid amendment of assessments, disagreements and disputes. It can cause also unnecessary extra work for both parties and may cause damage to organization’s reputation in public. The case study will be done for Finnish affiliated company, which parent company has been registered and located abroad. Valuation will be done both licensing and transferring of all rights ways. The Finnish case company develops constantly new technologies in research and development projects thus they must know how to make value determination for technologies if they are going to transfer of all rights or license their intellectual properties inside the consolidated organization. This study gives a good clearance about transfer pricing methods, rules and necessary legislation where they must pay attention when planning transfer pricing of intangible assets.
Keywords: transfer pricing; intangible assets; fi=Talousoikeus|en=Business Law|; fi=Talousoikeuden maisteriohjelma|en=Master's Programme in Business Law|; Yritysverotus